2011
DOI: 10.1093/jxb/err300
|View full text |Cite
|
Sign up to set email alerts
|

Low cadmium (LCD), a novel gene related to cadmium tolerance and accumulation in rice

Abstract: The contamination of food crops by cadmium (Cd) is a major concern in food production because it can reduce crop yields and threaten human health. In this study, knockout rice plants (Oryza sativa) tagged with the gene trap vector pGA2707 were screened for Cd tolerance, and the tolerant line lcd was obtained. The lcd mutant showed tolerance to Cd on agar plates and in hydroponic culture during early plant development. Metal concentration measurements in hydroponically grown plants revealed significantly less C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 22 publications
3
58
0
Order By: Relevance
“…[36][37][38]. The current studies have shown Cd transport in rice, tomato, tobacco, and radish by ZIP1 [16,32,[39][40]. In the present investigation, expression of ZIP1 increased significantly and quickly in the roots of S. matsudana for the early stage of 50 μM Cd treatments (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…[36][37][38]. The current studies have shown Cd transport in rice, tomato, tobacco, and radish by ZIP1 [16,32,[39][40]. In the present investigation, expression of ZIP1 increased significantly and quickly in the roots of S. matsudana for the early stage of 50 μM Cd treatments (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…rsa-miR156 targeted a transcript encoding a glutathione S -transferase 5 ( GST5 ), whereas rsa-miR393 targeted phytochelatin synthase 1 ( PCS1 ). In plant cells, one major mechanism related to Cd detoxification is complexation with a range of metal-chelating peptides such as glutathione (GSH) and phytochelatins (PCs), both of which reduced its mobility and sequestered the phytochelatin–metal complexes into the vacuole (Shimo et al ., 2011; Satoh-Nagasawa et al ., 2012). Moreover, detoxification of reactive oxygen species (ROS) could be accomplished by synthesis of various antioxidants such as ascorbate, GSH, and glutathione S-transferase (DalCorso et al ., 2008; Takahashi et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The OsNRAMP5, OsHMA3, OsHMA2, OsLCT1 and LCD regulated the uptake, transport and accumulation of Cd in rice (Ueno et al, 2010;Shimo et al, 2011;Uraguchi et al, 2011;Ishimaru et al, 2012;Sasaki et al, 2012;SatohNagasawa et al, 2012;Takahashi et al, 2012). The OsNRAMP1, OsFER2, OsYSL2, OsYSL15, OsYSL18, OsIRT1 and OsIRT2 contributed to transporting of Fe in rice (Curie et al, 2000;Bughio et al, 2002;Koike et al, 2004;Ishimaru et al, 2006;Nakanishi et al, 2006;Inoue et al, 2009;Aoyama et al, 2009;Takahashi et al, 2011;Paul et al, 2012).…”
Section: Discussionmentioning
confidence: 98%